Correlation of coagulation markers with axillary lymph node metastasis in breast malignancy: a tertiary care centre study in North India - Srivastava, Vaibhav; Rai, Nandan; Ahmad, Shabi; Singh, Vikram; Kumar, Shirish (International Surgery Journal, 2020)
Background: Breast cancer is the most common female cancer worldwide representing nearly a quarter (25%) of all cancers. Search for a marker which can predict lymph node metastasis in clinically negative axilla has been a matter of research for long. The present study is an attempt to evaluate role of coagulation makers with special reference to D-dimer and factor 7 and 8 in patients of carcinoma breast in predicting lymph node metastasis in carcinoma patients. Methods: The study was a prospective study conducted in 50 diagnosed patients of carcinoma breast in whom D dimer levels and factor 7 and 8 levels were measured at the time of commencement of the treatment and at six weeks after surgery. Results: Most of the patients in the study group were in the age group 41-70 (80%) years. 22% patients were of early Breast cancer. The reduction in D-dimer, factor VII and factor VIII value after 6 weeks of surgery were significant (p value 0.0001 for all three). Conclusions: D-dimer and factor VII were found to be an independent predictive factor for lymph node metastatsis, thus providing as a safe, easy, objective and convenient supplement to sentinel node biopsy in assessing metastatic disease in axilla. Combined- with other biomarkers, it may prove to be an alternative to sentinel node biopsy in assessing metastatic disease in axilla. Significant postoperative decrease in D-dimer, factor VII and factor VIII may provide objective criteria to assess completion of surgery.